Effectiveness of mineral water application on the functional state of the liver in individuals after cholecystectomy at the long-term rehabilitation stage as a prerequisite for creating individualized rehabilitation programs - Holod , Nataliia (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. Liver function in people after cholecystectomy is of great importance because it has vital functions. The purpose of the study is to determine the effectiveness of the use of mineral water on the functional state of the liver of people after cholecystectomy at the long-term stage of rehabilitation as a prerequisite for the creation of individual rehabilitation programs in the conditions of the Morshinkurort sanatorium-resort complex. Research methods: an analysis of 100 medical records of people after laparoscopic cholecystectomy was carried out. People used mineral diluted therapeutic water (DMW) of the well No. 3-k in the village of Horishne, Stryi district, Lviv region at a dilution of 3.0-3.4 g/dm3 when used internally. MRW is a product of dilution in certain proportions of underground brines from well No. 3-K and groundwater from source No. 4 in the city of Morshyn to a mineralisation of 3.0-3.4 g/dm3. Medical cards were selected by a randomized method using the Random Allocation Rule program. Blinding of evaluators in the processing of medical cards. Methods of mathematical statistics – Student’s t-test. The investigated indicators: total protein (g/l), thymol test (units), total protein, alanine transpeptidase (ALT, mmol (h.l.)), aspartate transaminase (AST, mmol (h.l.)), total cholesterol (mmol/l), triglycerides (un.l), blood sugar. The results. Impaired liver function in people after cholecystectomy in the long-term rehabilitation stage is a risk of developing metabolic syndrome. The use of mineral diluted therapeutic water from well No. 3 of the village of Horishne in a concentration of 3.0-3.4 g/dm3 for at least 14 days at the long-term stage of rehabilitation in persons after laparoscopic cholecystectomy led to a statistically significant difference (improvement) in the protein-synthesising function of the liver – the Thymol test decreased from 4.23±0.45 to 2.21±0.42 units (p<0.01). The activity of alanine transpeptidase ALT decreased, from 0.98±0.11 to 0.68±0.10 mmol/(h·l), (p<0.05), which indicates the recovery of liver cells. There was a decrease (p<0.05) in the total cholesterol level from 6.21±0.37 to 5.23±0.32 mmol/l. Conclusions. Hydrotherapy at the long-term stage of rehabilitation leads to improved liver function in people after laparoscopic cholecystectomy.